Integration of Liveworksheets in Student Worksheet Development: Practicality Analysis in Problem Based Learning Model - Susilawati; Utari, Viona Dwi; Permana, Niki Dian; Syarif, Muhammad Ilham; Putri, Dian Puspita Eka (Proceeding International Conference on Education, 2025)
This study aims to analyze the practicality of Liveworksheet integration in the development of Student Worksheets (LKPD) based on the Problem Based Learning (PBL) model. This integration is expected to create interactive LKPD that supports digital problem-based learning, in accordance with the demands of 21st-century learning. This study uses the Research and Development (R&D) method with a 4D development model consisting of the define, design, develop, and disseminate stages. The trial subjects were secondary-level students who participated in learning using Liveworksheet-based LKPD. Data were collected through teacher and student response questionnaires, and interviews. Practicality analysis was carried out by calculating the percentage of feasibility based on ease of use, clarity of instructions, and integration with PBL steps. The results showed that Liveworksheet-based LKPD has a very high level of practicality, with an average percentage above 85%, both in terms of ease of use and integration with PBL syntax. Thus, the integration of Liveworksheet in the development of LKPD can be an alternative interactive and practical learning media to support the implementation of PBL in the digital era.